First report of Oxysternon silenus Castelnau (Scarabaeidae, Scarabaeinae, Phanaeini) in the Brazilian Atlantic Forest - Filgueiras,Bruno K. C. (2011)
First report of Oxysternon silenus Castelnau (Scarabaeidae, Scarabaeinae, Phanaeini) in the Brazilian Atlantic Forest. This is the first record of Oxysternon silenus in the Brazilian Atlantic Forest. Specimens were collected in the Serra Grande landscape, municipality of Ibateguara, in Alagoas State. The samples were done from August 17 to 19, 2007 with pitfall traps. Before the present study, Oxysternon silenus had been reported predominantly in Amazonian region. The finding of this species corroborates the hypothesis of the biogeographical relationships between the Amazon Rainforest and the Atlantic Forest.